Effects of foliar application of copper sulphate and urea on the growth of lodgepole pine - Majid, Nik M.; Ballard, T.M. (1990)
A field study was conducted at three different locations in interior British Columbia, Canada, to assess lodgepole pine response to foliar application of copper sulphate and urea fertilizers. Results indicate that shoot growth and biomass production responded greatly to treatments only during the second growing season following fertilization. No significant positive tree growth response was detected during the year of fertilizer application. The highest response was obtained from treatment that caused minimal foliar scorching. The safe application dosage (where no foliar injury was evident) of copper sulphate was 0.1%. The application of 1% CuSO4 was extremely toxic to the trees. Results also indicated that the critical value for the Cu was found to be 4 ppm and Cu toxicity in lodgepole pine might occur whenever foliar Cu concentration exceeds 17 ppm. It was also found that foliar feeding of urea did not seem to have any physiological interaction with foliar Cu. Implications of foliar applications of micronutrient fertilizers in plantation forestry on a commercial basis are also discussed. © 1990.